Penerapan System Thinking Untuk Peningkatan Branding dan Optimalisasi Manajemen Usaha Pada UKM Handy Craft Az-Zahra - Arda Erico Yuda; Wahyu Andy Prastyabudi, S.Kom, MSc.; Muhammad Dzulfikar Fauzi, S.Kom., M.Cs; Arliyanti Nurdin , S.T., M.T (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
ABSTRACT MSMEs have an important role in the Indonesian economy, contributing about 60 percent of GDP. But on the other hand, the expansion of SMEs around us is still relatively low. Based on the 2016 BPS economic survey, 63.72 percent of entrepreneurs stated that there were no plans to develop their businesses for various reasons. Moreover, the Covid-19 pandemic has made MSMEs increasingly sluggish because the demand for their product sales has decreased drastically. This service aims to empower and strengthen the business management of the Handy Craft Az Zahra Creation UKM located in Surabaya. In particular, this service focuses on understandingpartners'e mindset and capacity building regarding business management, strengthening branding, and online marketing/distribution. The activity method used is to explore and map problems through direct observation and interviews with partners. Then formulate a solution with a systems thinking approach which is realized in a structured mentoring and training program. The results of this service will provide increased knowledge and managerial skills for partners to improve product quality, manage demand, and develop their business in a sustainable manner. The impact of this service in the future is expected to be a model for similar SMEs, so that the solution framework designed can be duplicated by other SMEs to help business development.. Keywords: business management, online marketing, branding, training, systems thinking